Traditional Chinese Medicine Monomers: Novel Strategy for Endogenous Neural Stem Cells Activation After Stroke - Wang, Ju; Hu, Jun; Chen, Xuezhu; Lei, Xuejiao; Feng, Hua; Wan, Feng; Tan, Liang (Frontiers in Cellular Neuroscience, 2021)
Stem cell therapy, which has become a potential regenerative medical treatment and a promising approach for treating brain injuries induced by different types of cerebrovascular disease, has various application methods. Activation of endogenous neural stem cells (NSCs) can enable infarcted neuron replacement and promote neural networks’ regeneration without the technical and ethical issues associated with the transplantation of exogenous stem cells. Thus, NSC activation can be a feasible strategy to treat central nervous system (CNS) injury. The potential molecular mechanisms of drug therapy for the activation of endogenous NSCs have gradually been revealed by researchers. Traditional Chinese medicine monomers (TCMs) are active components extracted from Chinese herbs, and some of them have demonstrated the potential to activate proliferation and neurogenesis of NSCs in CNS diseases. Ginsenoside Rg1, astragaloside IV (AST), icariin (ICA), salvianolic acid B (Sal B), resveratrol (RES), curcumin, artesunate (ART), and ginkgolide B (GB) have positive effects on NSCs via different signaling pathways and molecules, such as the Wingless/integrated/β-catenin (Wnt/β-catenin) signaling pathway, the sonic hedgehog (Shh) signaling pathway, brain-derived neurotrophic factor (BDNF), nuclear factor erythroid 2-related factor 2 (Nrf2), and heme oxygenase 1 (HO-1). This article may provide further motivation for researchers to take advantage of TCMs in studies on CNS injury and stem cell therapy.